Rancang Bangun Aplikasi Kas Rute12 Berbasis Web pada RT 012 RW004 Tanah Merdeka Jakarta Timur - Lestari, Sri; Ramadhanty, Irviani Liestian; Rachmawati, Dea Noer (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
The monthly contribution payment system at RT 012 RW 004 Tanah Merdeka, East Jakarta, still relies on a manual process using a contribution book, making it prone to errors and discrepancies between the money collected and the recording report. To overcome this problem, a web-based application has been developed called RUTE12. This application aims to simplify the tasks of RT officers in recording and managing finances while increasing community involvement. With the introduction of digitalization, it is hoped that it can reduce calculation errors, align the amounts collected with reports, and increase service efficiency. RUTE12 also plays a role in increasing community participation in various RT/RW activities, providing positive benefits for improving the financial system at the RT level, and being an inspiration for similar developments in various regions.